Values and Prosocial Behaviour in the Global Context: Why Values Predict Public Support for Foreign Development Assistance to Developing Countries. (May 2016) - Bayram, A. Burcu
Do basic human values facilitate prosocial behaviour on a global scale? This study, for the first time, analyzes the effect of values on prosocial behaviour in the context of public support for foreign development assistance. Support for foreign development assistance is a prosocial act intended to benefit the less fortunate in developing nations. Despite a plethora of evidence showing the effect of personal values on prosocial behaviour, the literature has neglected the value origins of support for development assistance. I argue that personal values play a crucial role in shaping individuals' support for foreign development assistance. Using data from nationally representative samples covering 11 Organisation for Economic Cooperation and Development (OECD) countries, I show that self-transcendence and openness to change values, as defined by Schwartz' theory of values, are reliable predictors of support for foreign development assistance. By linking human values to foreign development aid, this study expands the purview of values research to the domain of global governance and opens up new avenues of interdisciplinary inquiry that apply theories of values to different dimensions of world affairs.